2018
DOI: 10.1044/persp3.sig12.99
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Not Addressing the Communication Barriers Faced by Hospitalized Patients

Abstract: Preventable adverse events (AEs) lead to poorer patient outcomes, added patient suffering and dissatisfaction, longer hospital stays, and billions in additional annual healthcare spending. Patients facing barriers to communication are three times more likely to experience a preventable adverse event than patients who faced no communication barriers. National data on hospital admissions, incidence and cost of preventable AEs, and the odds ratio regarding the risk of preventable AEs in people facing communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…28 Facilitating speech may enhance safety, comfort, and quality of care, by enabling both self-expression and communication of symptoms to HCP. 27,29 The most serious adverse events described were subcutaneous emphysema, 18 and cuff rupture following an incorrect procedure. 22 These adverse events were not caused by the ACV method itself, but by procedure deviation and incorrectly placed tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…28 Facilitating speech may enhance safety, comfort, and quality of care, by enabling both self-expression and communication of symptoms to HCP. 27,29 The most serious adverse events described were subcutaneous emphysema, 18 and cuff rupture following an incorrect procedure. 22 These adverse events were not caused by the ACV method itself, but by procedure deviation and incorrectly placed tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…When patients test positive for SARS-CoV-2, the recommendation is to place them in a negative pressure room with strict requirements for contact and airborne precautions as well as PPE to prevent viral transmission [ 4 ]. This recommendation helps to protect other hospitalized patients as well as healthcare providers from contracting the virus and spreading it to other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have examined the psychological impact of isolation for contact precautions among patients. Being placed on isolation has been associated with shorter and fewer interactions with healthcare workers, more depressive symptoms, prolonged hospital stay, and lower standards of care [ 4 ]. A case-control study investigating the effect of isolation on hemodialysis patients with multidrug-resistant organism colonization demonstrated that adopting contact precautions and isolation can further negatively impact social functioning, sleep, and quality of life [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transposed to the level of physician-patient interaction, the paradoxical effect of repetition and of difference evidences beyond any doubt that the dialogue is a heterogeneous one, impossibly to be compared among either physicians or hospitals. Such a situation creates major barriers in medical communication (16). Apart from good command over the medical knowledge in his domain, for granting highquality services to his patients, a doctor should also master the inter-human dialogue.…”
Section: Theory and Practice: Difficulties And Tensions In Healthcarementioning
confidence: 99%